1983
DOI: 10.1111/j.1399-6576.1983.tb01964.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway Complaints and Laryngeal Pathology after Intubation with an Anatomically Shaped Endotracheal Tube

Abstract: In a group of 100 patients intubated with standard polyvinyl chloride (PVC) endotracheal tubes, 26 spontaneously complained of airway discomfort postoperatively. A further 55 patients complained of airway discomfort upon direct questioning. In a comparison group of 100 patients intubated with PVC orotracheal tubes shaped to conform with the anatomy of the airway, the corresponding figures were 14 and 21. Laryngoscopy before and 5 days after intubation revealed that among patients intubated with standard tubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…In a study of 200 patients in which intubation with a standard polyvinylchloride (PVC) tube was compared with that with a tube shaped to conform to the anatomy of the airway, patients underwent indirect laryngoscopy 5 days postoperatively [43]. Similar numbers of patients in each group had pathological changes (32% in the standard PVC group, 23% in the study group), but lesions were seen more frequently in the interarytenoid and subglottic area when the standard PVC tube was used.…”
Section: Injuries Resulting From Tracheal Intubationmentioning
confidence: 99%
“…In a study of 200 patients in which intubation with a standard polyvinylchloride (PVC) tube was compared with that with a tube shaped to conform to the anatomy of the airway, patients underwent indirect laryngoscopy 5 days postoperatively [43]. Similar numbers of patients in each group had pathological changes (32% in the standard PVC group, 23% in the study group), but lesions were seen more frequently in the interarytenoid and subglottic area when the standard PVC tube was used.…”
Section: Injuries Resulting From Tracheal Intubationmentioning
confidence: 99%
“…The principal cause of modification in zone H is the structural change in the head as a function of body position. This influence has already BRITISH JOURNAL OF ANAESTHESIA been reported by Alexopoulos and his colleagues in their work on a new intubation device [8][9][10][11][12][13]. The changes in cervicocephalic angle imply significant deformations in the pharyngolaryngeal structures.…”
Section: Discussionmentioning
confidence: 73%
“…Mean (SD) cervicocephalic angle(8) and area between curve segments and the X axis for the cervicocephalic angle subgroups.…”
mentioning
confidence: 99%
“…This does not touch the vocal folds, there should therefore be a minimal risk of laryngeal damage or discomfort. After tracheal intubation with direct contact with the vocal apparatus, the pos‐ sibility of post‐anaesthetic airway complaints is recognized [1–12]. On the other hand, studies have shown laryngeal discomfort after using a face mask with incidences as high as 33%[12, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Many different variables can influence the incidence and magnitude of the post‐anaesthetic sequelae. These include the material, shape and size of the tube, cuff pressure, drugs used and the general morbidity of the patient [5–10]. The way of questioning (direct or indirect) also influences the reporting of a sore throat [6, 11, 12].…”
Section: Introductionmentioning
confidence: 99%